Owning my thoughts was difficult: Encouraging students to read and write critically in a tertiary qualitative research methods course - Wiles, Janine; Allen, Ruth; Butler, Rachael (Journal of University Teaching and Learning Practice, 2016)
This paper adds to the nascent literature on teaching research methods and what students learn from courses and assessment. Postgraduate students are often confronted with large amounts of reading, and the content of material can be intimidating. Convincing them also to engage critically with readings is even more difficult. We report on a successful strategy used to help postgraduate students in a qualitative research methods course develop the skills to read efficiently and critically. We outline the synopsis method and report on an evaluation of students’ experiences of it as an assessment and learning tool.Evaluation showed that students saw their learning experience as challenging and rewarding and could articulate how the synopsis method was useful for specific reading/writing skills, critical engagement and reflexivity, content knowledge, and motivation. We were surprised students found it novel to be asked to question or critique ‘published’ papers and articulate subjective reflections on them. Our evaluation shows that the synopsis method is an effective learning strategy to improve students’ critical reading and writing skills.We argue that in learning the craft of qualitative research, students must understand not only how to summarise and critique but must also master the skill of articulating personal, reflexive responses.